PENGARUH KUALITAS PELAYANAN, KEBIJAKAN HARGA TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN PADA JASA LAPANGAN INTERNASIONAL FUTSAL PEKANBARU - Sukpa, Wiwik Dwi; Wijayanto, Gatot; ', Taufiqurrahman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine how the variables influence service quality, pricing policy towards customer satisfaction and loyalty simultaneously or partially on international futsal field services pekanbaru. This study uses the technique of accidental sampling method sampling conducted by coincidence. To determine the number of samples using Slovin formula, and obtained a sample of 96 people from a total population of 2268 people. This study uses primary data, where the data obtained through interviews and questionnaires. The method used is the analysis of the path (path analysis) with SPSS version 16. Simultaneous regression (F test) showed that the independent variables (quality of service and pricing policies) simultaneously have significant effect on the dependent variable (satisfaction and loyalty. Magnitude of the effect that (R2) by these two independent variables together amounted to 85% of the dependent variable, while the rest is influenced by other variables not examined in this study. Results of the testing that has been done, the partial regression test (t test) showed that service quality contributes significantly to customer satisfaction, price contributes significantly to customer satisfaction , quality of service is directly contributed significantly to customer loyalty, price directly contributes significantly to customer loyalty, service quality, price and customer satisfaction simultaneously and significantly contribute to customer loyalty at 84.4%.Keywords: Quality of Service, Price Policy, Satisfaction, Quality of Customer